Constructing Justice-Based Political Party Regulation in Indonesia's Presidential System: A Framework for Democratic Consolidation - Hafiz Sutrisno; Rian Prayudi Saputra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study looks at how Indonesia's presidential system regulates political parties from a justice-based point of view, using qualitative methods like document analysis, content analysis, and comparative studies. The results show that Indonesia's political party rules, which are based on Laws No. 2 of 2008 and No. 2 of 2011, have a lot of problems that make the presidential system less effective. The current rules are not fair because they favor procedural over substantive aspects. This is because the major parties control access to political resources. There are three main types of justice: distributive justice, which is about making sure political resources are fairly shared; procedural justice, which is about making sure political processes are fair; and substantive justice, which is about making sure that society's needs are met. A perfect model for building rules needs a full and integrated framework, easy ways for people to raise money, organized coalition systems, and stronger roles for political parties as representatives. Oligarchic elites don't want rules that are fair, and Indonesia's many cultures make it harder to make them happen. But there is still hope for change if people work together and share power. This study helps us figure out how to make Indonesia's democratic presidential system stronger by making sure that the rules we set for political parties fit the country's needs.